2020
DOI: 10.1163/22941932-bja10031
|View full text |Cite
|
Sign up to set email alerts
|

Ray properties in the stems of Dahurian larch (Larix gmelinii) and Japanese larch (Larix kaempferi)

Abstract: The radial variation of rays within the stems of Dahurian larch and Japanese larch growing in Korea was studied to obtain valuable information to identify the two species and determine wood quality. Uniseriate ray height, fusiform ray height, ray number, ray spacing, and epithelial cell number were investigated by optical microscopy. The heights of uniseriate and fusiform rays and epithelial cell numbers in Dahurian larch were lower than those in Japanese larch. Dahurian larch wood had greater ray number and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 15 publications
3
5
0
Order By: Relevance
“…For both species, the average ray numbers of juvenile wood were significantly higher than those of mature wood (p < 0.01, Table 2). This is consistent with the previous studies; the ray number in coniferous wood decreased with increasing the number of the growth ring and became a constant in mature wood [10,35,36]. The violin plot confirmed that juvenile wood of both species has higher first, median, and third quartile values than their corresponding mature wood (Figure 2e) because the largest numbers of the ray cambial initials are formed during the early juvenile years when peripheral expansion of the cambium is greatest [21].…”
Section: Ray Traitssupporting
confidence: 93%
See 4 more Smart Citations
“…For both species, the average ray numbers of juvenile wood were significantly higher than those of mature wood (p < 0.01, Table 2). This is consistent with the previous studies; the ray number in coniferous wood decreased with increasing the number of the growth ring and became a constant in mature wood [10,35,36]. The violin plot confirmed that juvenile wood of both species has higher first, median, and third quartile values than their corresponding mature wood (Figure 2e) because the largest numbers of the ray cambial initials are formed during the early juvenile years when peripheral expansion of the cambium is greatest [21].…”
Section: Ray Traitssupporting
confidence: 93%
“…As shown in Figure 2d, the violin plot of ray spacing presents a fluctuation around the 6/mm for Masson pine. An obvious decrease is shown in Chinese fir from juvenile wood to mature wood, in accordance with the decrease in the ray spacing of Larix gmelinii and Larix kaempferi as the growth ring number increased [10]. It should be emphasized that, according to the hypothesis proposed by Carmi et al [34] and Lev-Yadun and Aloni [12], ray spacing is controlled by excess stimuli, such as the hormone ethylene, which has a negative effect on polar auxin transport, and in turn, affects the formation of ray initials and the enlargement of existing ones.…”
Section: Ray Traitssupporting
confidence: 57%
See 3 more Smart Citations